1986
DOI: 10.1002/j.1460-2075.1986.tb04236.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of cat muscle pyruvate kinase.

Abstract: The complete amino acid sequence of cat muscle pyruvate kinase has been determined and fitted to the 2.6 A resolution electron density map. Residues in the active site region are highly conserved in the cat muscle, chicken muscle, rat liver and yeast enzymes. The enzyme‐bound magnesium, which is essential for activity, interacts with the side chain of glutamate‐271 and with two main carbonyl groups. Lysine‐269 is the probable acid/base catalyst responsible for the interconversion of pyruvate and enolpyruvate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
193
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(194 citation statements)
references
References 32 publications
1
193
0
Order By: Relevance
“…The X-ray diffraction studies on cat M1 PK [6] have revealed the complex molecular architecture of the enzyme, which is a tetramer of four identical subunits, each encompassing three domains (see Fig. 2A The reaction is catalysed by pyruvate kinase (PK), which requires for its activity both monovalent and divalent cations [1,2].…”
Section: Overall Architecturementioning
confidence: 99%
See 4 more Smart Citations
“…The X-ray diffraction studies on cat M1 PK [6] have revealed the complex molecular architecture of the enzyme, which is a tetramer of four identical subunits, each encompassing three domains (see Fig. 2A The reaction is catalysed by pyruvate kinase (PK), which requires for its activity both monovalent and divalent cations [1,2].…”
Section: Overall Architecturementioning
confidence: 99%
“…Glycolysis; Metabolism regulation; X-ray crystallography; Pyruvate kinase whereas the L PK is additionally controlled by phosphorylation on a N-terminal Ser residue which causes a decrease in the affinity for the PEP and FBP activators [3]. More unusual is the muscle M1 protein [6] which is the only known PK displaying hyperbolic kinetics and no allosteric control.While the structure of the cat M1 isoenzyme was determined by Muirhead and coworkers several years ago [6], little information was available about the allosteric transition in PK. Substantial progress in this respect has been observed over the last few years with further refinement of the M1 isoenzyme model [7], and with the X-ray structure determination of the FBP-dependent E. coli PK, in the inactive T-state [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations